Perbandingan Double Exponential Smoothing dan Triple Exponential Smoothing untuk Peramalan Jumlah Produksi Padi di Kota Surakarta - Moch Irfan Prayudha Adhianto; Fitra Abdurrachman Bachtiar; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Every day, humans consume staple food as a source of energy to carry out daily activities. Most people, especially in the city of Surakarta, consume rice as a staple food made from rice in the rice plant. Therefore, rice is the most important crop in the city of Surakarta. The city government of Surakarta hopes that rice production will always increase. However, with the weather, employment, city planning, and other factors can cause the development of rice production to decline. With this, the city government of Surakarta cannot know when rice production has decreased. Therefore, with this forecasting research, it is hoped that it can help the Surakarta city government in cultivating these rice plants. This rice production forecasting system is designed using two methods as a comparison, namely: Double Exponential Smoothing and Triple Exponential Smoothing. The data used is data from Badan Pusat Statistik (BPS) Kota Surakarta. By using the alpha, beta value parameter in the Double Exponential Smoothing and the alpha, beta, and gamma value Triple Exponential Smoothing methods, it is found that the MAPE (mean absolute error error) value of the Double Exponential Smoothing method is 39.31 with the best combine alpha and beta value of 0.4 & 0.2. Meanwhile, the MAPE value of the Triple Exponential Smoothing method is 31.65. with the best combine alpha, beta, gamma value of 0.4, 0.1, & 0.9.